Maqāṣid al-Syarī‘ah in Islamic Jurisprudence and Transgender Rights: A Comparative Analysis of Fatwas in Egypt and Iran - Abidin, Zainal; Aziz, Fajar Rahmat; Asdar, A.; Hijaz, M. Chiar (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This article examines how Islamic jurisprudence engages with transgender rights through two landmark fatwas in Egypt and Iran: Sheikh Muhammad al-Tantawi’s 1988 fatwa and Ayatollah Ruhollah Khomeini’s 1987 fatwa. Using qualitative methods—document analysis, hermeneutics, and comparative case studies—the study analyzes how religious authorities interpret sex reassignment surgery (SRS) within Islamic law. Al-Tantawi permits SRS only for intersex individuals, reinforcing binary gender norms and sustaining legal ambiguity and social stigma in Egypt, though his ruling nonetheless inspired activism for more inclusive interpretations. In contrast, Khomeini’s fatwa employs theological principles such as aṣālat al-ibāḥa (original permissibility) and taslīṭ (personal authority) to allow SRS for transgender individuals diagnosed with gender dysphoria, shaping Iranian state policy through formal medical protocols and insurance coverage. However, tensions remain, as this recognition coexists with the criminalization of homosexuality. The study shows that while medical diagnostics are central to legitimizing contemporary fatwas in both countries, such reliance also reinforces the pathologization of gender variance. By foregrounding this tension, the article demonstrates how medicalization both enables and constrains Islamic legal reasoning. It argues that applying maqāṣid al-Sharīʿa—particularly justice, welfare, and human dignity—offers a more compassionate and ethically responsive framework. The findings highlight the need for expanded ijtihād that incorporates non-binary and intersectional identities to support a more inclusive, human-centered Islamic legal approach.